Easements and Conservation Policy in the North Maine Woods - Lewis, David (Maine Policy Review, 2001)
Recently Maine has embarked on a new policy direction in its use of conservation easements to protect large tracts of commercial timberland. David Lewis argues that the effectiveness of using easements as a long-term conservation policy depends on many factors that may not be fully considered in the decision-making process currently used in choosing easements for landscape-scale conservation. Lewis indicates that the root of the problem lies in the fact that the state lacks a comprehensive policy describing the conservation goals desired in the North Woods. Before progressing further, Lewis suggests that the ultimate goals of conservation need to be understood clearly. Is conservation addressing development? Recreation needs? Biodiversity protection? Forest fragmentation? Moreover, what are the costs and benefits associated with the state’s various conservation options?